Spring retained surgical obturator followed by closed hollow definitive obturator using lost wax bolus technique in a total maxillectomy patient- a case report - Abhishek Kumar Gupta; Gupta Rekha; Gill Shubhra (Journal of Oral Biology and Craniofacial Research)
Total maxillectomy is referred to as bilateral resection of maxillae in patients suffering from a benign, malignant neoplasm or chronic infections like osteomyelitis, etc. It causes communication between the oral and antral cavity extending to the nasopharynx. A complete bilateral maxillectomy defect presents a considerably reconstructive challenge for the prosthodontist because of the absence of normal hard and soft tissues for the support of prosthesis. The surgical obturator was retained via spring which develops the seal between the acrylic plate and the dorsum of the tongue during deglutition, thus helping the patient to take a soft diet orally during the healing period. The definitive conventional closed bulb hollow obturator fabricated using the “lost wax bolus” technique, is a reliable and feasible treatment option to restore the total maxillectomy defect, thus improving and enhancing the quality of patient’s life and livelihood.